Graduate Student Literature Review: The DRB3 gene of the bovine major histocompatibility complex—Discovery, diversity, and distribution of alleles in commercial breeds of cattle and applications for development of vaccines* - Thales Eduardo Galdino Andrade; Maurício Scavassini Peña; Jéssica Fiorotti; Renan de Souza Bin; Alexandre Rodrigues Caetano; Timothy Connelley; Isabel Kinney Ferreira de Miranda Santos (Journal of Dairy Science)
ABSTRACT: The bovine major histocompatibility complex (MHC), also known as the bovine leukocyte antigen (BoLA) complex, is the genomic region that encodes the most important molecules for antigen presentation to initiate immune responses. The first evidence of MHC in bovines pointed to a locus containing 2 antigens, one detected by cytotoxic antiserum (MHC class I) and another studied by mixed lymphocyte culture tests (MHC class II). The most studied gene in the BoLA region is the highly polymorphic BoLA-DRB3, which encodes a β chain with a peptide groove domain involved in antigen presentation for T cells that will develop and co-stimulate cellular and humoral effector responses. The BoLA-DRB3 alleles have been associated with outcomes in infectious diseases such as mastitis, trypanosomiasis, and tick loads, and with production traits. To catalog these alleles, 2 nomenclature methods were proposed, and the current use of both systems makes it difficult to list, comprehend and apply these data effectively. In this review we have organized the knowledge available in all of the reports on the frequencies of BoLA-DRB3 alleles. It covers information from studies made in at least 26 countries on more than 30 breeds; studies are lacking in countries that are important producers of cattle livestock. We highlight practical applications of BoLA studies for identification of markers associated with resistance to infectious and parasitic diseases, increased production traits and T cell epitope mapping, in addition to genetic diversity and conservation studies of commercial and Creole and locally adapted breeds. Finally, we provide support for the need of studies to discover new BoLA alleles and uncover unknown roles of this locus in production traits.